The Effect of Financial Literacy, Financial Inclusion, Fintech Crowdfunding on MSME Performance in Sidoarjo Regency: Pengaruh Literasi Keuangan, Inklusi Keuangan, Fintech Crowdfunding Terhadap Kinerja UMKM di Kabupaten Sidoarjo - Dewi, Ajeng Listyo; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2022)
In 2020, Indonesia and even the world experienced a COVID-19 pandemic. As a result, many aspects of life were affected by the COVID-19 pandemic, including the economic aspect. One of the efforts to rebuild the economic aspect is to encourage the performance of MSMEs in a country. MSMEs are an important engine to encourage a country's economic growth. This study aims to develop previous research on the effect of financial literacy, financial inclusion, and fintech crowdfunding on MSME performance in the Sidoarjo Regency. This study used cluster random sampling as a sampling technique. A total of 177 MSME owner-manager questionnaire data were processed using multiple linear regression analysis. The results of the study prove that there is a positive and significant influence between financial literacy on the performance of MSMEs, financial inclusion has a positive and significant effect on the performance of MSMEs, and fintech crowdfunding has a negative and insignificant effect on the performance of MSMEs. This study shows that MSME business owners need to be technology and financial literate because it can enable them to make good financial decisions to ensure the sustainability of their business.